Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Agro Boga Utama Cabang Jakarta Selatan - Oktaviana Sai; Yeni Septiani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - This research aims to analyze the influence of Work Environment and Work Motivation on Employee Performance at PT Agro Boga Utama, South Jakarta Branch. The research method used is descriptive with a quantitative approach. The population in this study consisted of 65 employees, all of whom were used as the sample through a saturated sampling technique. Primary data were obtained through observation, questionnaires, literature study, and documentation. The data analysis included descriptive statistical tests, research instrument tests, classical assumption tests, simple linear regression, multiple linear regression, correlation coefficient (R) test, coefficient of determination (R-Square) test, and hypothesis testing. The partial results show that the Work Environment has a positive and significant effect on Employee Performance, indicated by a t-value of 8.757, which is greater than the t-table value of 1.999, with a significance level of 0.000, which is smaller than the p-value of 0.05. Furthermore, Work Motivation also has a positive and significant effect on Employee Performance, with a t-value of 9.280, which is greater than the t-table value of 1.999, and a significance level of 0.000, which is below the p-value threshold of 0.05. Simultaneously, the Work Environment and Work Motivation variables have a positive and significant effect on Employee Performance, as indicated by an F-value of 56.105, which exceeds the F-table value of 3.145, with a significance level of 0.000, also below the p-value of 0.05. The simultaneous coefficient of determination (R-Square) value of 0.644 shows that the Work Environment and Work Motivation explain approximately 64.4% of the variation in Employee Performance, while the remaining 35.6% is influenced by other factors not examined in this study.